Conflict-solving as a mediator between customer incivility and service performance - USLU, AYPAR (My University, 2022)
The customer incivility literature has primarily focused on emotional exhaustion and burnout as emotion-focused mediators that channel the effect of customer incivility. Drawing on conservation of resources (COR) theory, the current research proposes a new problem-solving-focused mediator, namely, conflict-solving behavior. The authors test the mediating role of conflict-solving behavior between customer incivility and customer service performance while controlling for emotional exhaustion and employee incivility as parallel mediation mechanisms. The results from three studies provide strong support for a negative relationship between customer incivility and conflict-solving behavior and for conflict-solving behavior as a full mediator between customer incivility and customer service performance. Furthermore, the negative effect of customer incivility on conflict-solving behavior is mitigated when customer service employees are promotion-focused and as investment in customer relationship building increases. The findings extend the scope and generalizability of customer incivility research from the business-to-customer to the business-to-business context. Managerial implications for employee training and hiring as well as the importance of cultivating customer relationships as a buffer to dampen the effect of customer incivility are discussed.

客户不文明行为的相关文献主要将情绪相关变量作为解释客户不 文明行为的影响的中间变量，例如情绪衰竭和过度疲劳。本文借 鉴资源保存理论（COR），提出了一种新的以问题为中心的中间 变量，即冲突解决行为。作者测试了冲突解决作为影响在客户不 文明和客户服务绩效之间的中间变量作用，同时控制了情绪衰竭 和员工不文明作为平行中间变量。三项研究结果均有力地支持了 客户不文明行为与冲突解决行为之间的负向关系，同时表明了冲 突解决行为是客户不文明行为与客户服务绩效之间的完全中间变 量。另外，当客户服务员工是专注促销的时候，以及对建立客户 关系的投资增加的时候，客户不文明行为对于冲突解决的负面影 响将会得到减少。研究结果将客户不文明行为研究的范围和普适 性从企业对消费者（B2C）扩展到企业对企业（B2B）的商业环 境。本研究在对管理者的启示部分也讨论了员工培训和招聘以及 培养客户关系的重要性作为抑制客户不文明影响的缓冲作用。
论冲突解决作为客户不文明行为和服务绩效之间的中间变量
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; YÖNETİM; Ekonomi ve İş; Sosyal Bilimler (SOC); MANAGEMENT; ECONOMICS & BUSINESS; Social Sciences (SOC); Genel Karar Bilimleri; Karar Bilimleri (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; General Decision Sciences; Decision Sciences (miscellaneous); Social Sciences & Humanities; Customer incivility; conservation of resources; regulatory focus theory; conflict solving; customer relationship; REGULATORY FOCUS; EMOTIONAL EXHAUSTION; PROBING INTERACTIONS; EMPLOYEE; MULTILEVEL; CONSERVATION; RESOURCES; BEHAVIOR; MISTREATMENT